On the importance of financial instruments to facilitate growth - Ellitsa Dalampoura; Michael Polemis (SPOUDAI - Journal of Economics and Business, 2021)
Small and Medium-Sized Enterprises (SMEs) constitute the backbone of all market economies worldwide; the EU is not an exception. As such, they merit particular attention from the part of the public authorities, in times of financial crisis when alternative financing sources are needed. Traditionally, the public authorities, being at the European or national level, used subsidies to assist SMEs in activities presenting some investment risk, and /or enhancing entrepreneurial high value-added export-oriented activities, producing tradable goods. This study presents the way financial instruments (FIs) were introduced into the European Union (EU) programs supporting SMEs during the financial and economic crisis and the intervention logic behind them.
Keywords: L26; L38; M21; 330; SMEs; Subsidies; Financial instruments; Leveraging; Financial crisis